A Qualitative Study of Students with Behavioral Problems Participating in Service-Learning - O'Connor, Michael P. (Journal of the American Academy of Special Education Professionals, 2008)
This qualitative study examined the use of service-learning in an alternative high school that primarily serves students at-risk for educational failure due to behavioral problems. Interviews with students, teachers, and administrators, as well as observations and archival documents yielded three major categories of student benefits: (a) increased school engagement (b) personal growth (c) increased positive engagement with community. These findings are discussed with regard to curriculum and placement decisions for students with severe behavioral problems. Based on these findings and the research literature, service-learning is suggested as a teaching strategy with significant potential for serving the unique educational needs of these highly at-risk students.